Exploring the speech and language of individuals with non‐syndromic submucous cleft palate: a preliminary report. Issue 5 (2nd May 2019) - Boyce, Jessica O.; Sanchez, Katherine; Amor, David J.; Reilly, Sheena; Da Costa, Annette; Kilpatrick, Nicky; Morgan, Angela T.
Abstract: Background: Submucous cleft palate (SMCP) has a heterogeneous presentation and is often identified late or misdiagnosed. Diagnosis is prompted by speech, resonance or feeding symptoms associated with velopharyngeal insufficiency. However, the broader impacts of SMCP on communication have rarely been examined and therefore are poorly understood. Aim: To describe the communicative profile of individuals with non‐syndromic SMCP by examining speech, language and pragmatics (social language). Methods & Procedures: Fifteen participants with SMCP aged 5;1–12;8, without a genetic diagnosis, participated in the study. Participants completed standardized assessments examining language, resonance, speech and non‐verbal intellect. Parents also completed the Children's Communication Checklist (CCC‐2), which provided a measure of overall communicative ability, including pragmatic skills. Formal language outcomes were compared with two cohorts: 36 individuals with overt non‐syndromic clefts and 129 individuals with no history of clefting. Outcomes & Results: Speech intelligibility was reduced secondary to hypernasality, disordered articulation and/or impaired phonology ( n = 7) in children with SMCP. Poorer overall language outcomes were observed for children with SMCP compared with both those with overt clefts and no history of clefting ( p < 0.001). Language scores for children with SMCP ranged from impaired ( n = 6) to above the standardized mean ( n = 4). Receptive and expressive language performance were independently correlated with non‐verbal IQ ( p < 0.01). Those with severe language impairment ( n = 4) also had borderline or impaired non‐verbal IQ. Parents reported that speech and semantics were the most affected sub‐domains of communication, while scores were the highest for the initiation domain. Speech and language skills were correlated strongly with pragmatics ( r = 0.877, p < 0.01). Conclusions & Implications: Overall, performance was variable within the SMCP group across speech, language and pragmatic assessments. In addition to well‐documented speech difficulties, children with SMCP may have language or pragmatic impairments, suggesting that further neurodevelopmental influences may be at play. As such, for individuals with SMCP, additional clinical screening of language and pragmatic abilities may be required to ensure accurate diagnosis and guide both cleft and non‐cleft related therapy programmes.